Le Choeur des Grenouilles (Aristoph. Ran. 209-68): Musique et pas seulement! - Angela M. Andrisano (Annali Online dell'Università di Ferrara. Sezione Lettere)
The article criticizes those studies which maintain that the secondary chorus was not visible to the audience. Through a detailed philological analysis of vv. 1-284 and a dramaturgic approach to the entire comedy the author speculates about a possible choreography aimed to censoring the mimetic features of the new dithyramb.